Development of Blog-Based Learning Media With Sarong Context on Lines and Angles Material - Andita, Sintia; Syutaridho, Syutaridho; Nizar, Harisman (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This study aims to produce learning media based on blogs with the context of covers on lines and angles material using the PMRI approach which was valid, practical and has a potential effect on the ability to understand mathematical concepts in class VII students of SMP LTI IGM Palembang. The research method used was the development research method using the Tessmer flow (1993) which consists of the preliminary stage (preparation and design stages) and the formative evaluation stage, namely self-evaluation, expert review, one-to-one, small group and field tests). Data collection was carried out using validation sheets, questionnaires, interviews and tests. From the results of the study it was concluded that the blog-based mathematics learning media developed was qualitatively valid in terms of comments and suggestions from the validator, besides that quantitatively the percentage of validity was 4.129 and practically both qualitatively and quantitatively by looking at the comments and suggestions it was stated that blog-based learning media was practically used and the result of the analysis of the practical average of the questionnaire calculation is 76.263. Then the results of a high potential effect on students' conceptual understanding abilities with an average of 82.033.